Seasonal flight activity of Adult Amphipsyche meridiana Ulmer 1902 (Trichoptera: Hydropsychidae) in an Irrigation Pond Outlet - Panich-Pat, Thanawan; Suksa-Ard, Solaya; Prommi, Taeng On (Journal of Food Health and Bioenvironmental Science, 2019)
Seasonal flight activity of adult Amphipsyche meridiana Ulmer 1902 (Trichoptera: Hydropsychidae) in an irrigation pond outlet at Kasetsart University, Kamphaeng Saen Campus, Nakhon Pathom Province were investigated, with the influence of air temperature, wind speed, precipitation and relative humidity on its population density being evaluated. Samples were collected monthly from January to December 2016 by light trapping. Monthly sample records for adults collected were 3054, 6396, 576, 6654, 9228, 3222, 3402, 7974, 1950, 3483, 5016 and 5178, respectively. An increase in the number of adults collected was observed from April to May with peaks of 9,228 (16.48%) in May. A remarkable decrease in the number of insects collected was observed in the month after September. There was an increase in the number of adults with an increase in wind speed. Changes in the temperature, relative humidity and precipitation had less influence on seasonal flight activity of adult A. meridiana.